Hybrid ultrasound MRI for improved cardiac imaging and real-time respiration control - Feinberg, David A.; Giese, Daniel; Bongers, D. Andre; Ramanna, Sudhir; Zaitsev, Maxim; Markl, Michael; Günther, Matthias (Magnetic resonance in medicine, 2010)
A hybridized dual-imaging system combining real-time ultrasound imaging and MRI was utilized for cardiac imaging at 1.5 T and 3 T. The ultrasound scanner with a programmable software interface was connected via computer to the MRI scanner. Electronic noise was eliminated with electromagnetic shielding and grounding to the screen room. At 3 T, real-time prospective motion compensation in dynamic cine cardiac imaging was implemented using B-mode ultrasound imaging. The ultrasound technique avoided drawbacks such as signal saturation or steady-state interruption of the MR navigator gating. At 1.5 T, a low-latency real-time feedback to balanced steady state free precision MR imaging was performed in three normal volunteers. Results showed active tracking of the heart during respiratory motion and improvement in time-averaged cardiovascular images. Future studies can fully exploit the potential of the high-frequency position information provided by the ultrasound system for more advanced applications in real-time organ tracking. Magn Reson Med, 2010. © 2009 Wiley-Liss, Inc.
Gesehen am 15.08.2023